2018
DOI: 10.1177/1358863x18775593
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive stent use during endovascular intervention to the femoropopliteal artery with drug coated balloons: Insights from the XLPAD registry

Abstract: With growing use of drug-coated balloons (DCB) for femoropopliteal (FP) artery interventions, there is limited information on rates of real-world adjunctive stent use and its association with short and long-term outcomes. We report on 225 DCB treated FP lesions in 224 patients from the Excellence in Peripheral Artery Disease (XLPAD) registry (NCT01904851) between 2014 and 2016. Cochran-Mantel-Haenszel and Wilcoxon rank sum statistics were used to compare stented (planned or 'bail-out') versus non-stented DCB t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…[27][28][29][30] Among patients treated with DCB for FPAD in the XLPAD (Excellence in Peripheral Artery Disease) Registry study, the lesion length was significantly longer in patients who received an adjunctive stent compared with those who did not. 31 The results of this study also indicated that as the length of the CTO lesion increased, the primary patency rate of DA + DCB decreased significantly. In addition, all the 4 patients who received stent implantation at the reintervention procedure of target lesion within 1 year had CTO >10 cm.…”
Section: Discussionsupporting
confidence: 55%
“…[27][28][29][30] Among patients treated with DCB for FPAD in the XLPAD (Excellence in Peripheral Artery Disease) Registry study, the lesion length was significantly longer in patients who received an adjunctive stent compared with those who did not. 31 The results of this study also indicated that as the length of the CTO lesion increased, the primary patency rate of DA + DCB decreased significantly. In addition, all the 4 patients who received stent implantation at the reintervention procedure of target lesion within 1 year had CTO >10 cm.…”
Section: Discussionsupporting
confidence: 55%
“…For bailout stenting, nitinol stents were used most frequently (50%) followed by DES (34%) and BMS (22%). Similar short and intermediate-term clinical outcomes were obtained compared to non-stented lesions (22). Moreover, several DCB studies show a need for bail-out stenting in 10.7 % to 35.7% of DCB procedures (20,(23)(24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 59%
“…Table 1 lists real-world registries and single-center studies that have examined different endovascular treatments for complex femoropopliteal disease. 4,720 Clearly, the IN.PACT Global clinical cohort has complex disease presentations comparable to these other real-world studies. Unfortunately, we do not see homogeneity in the nomenclature for complex real-world femoropopliteal lesions across the different databases and registries.…”
Section: Putting the Study To The Testmentioning
confidence: 58%